PENGARUH KOMPETENSI TERHADAP KINERJA PENGELOLA BADAN USAHA MILIK DESA (BUMDES) DI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - ,Kurniawaty Fitri, Dhea Salwa ,Raden Lestari Ganarsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The research was carried out at village owned enterprises (BUMDes) which are included in the basic clasification in kuantan singingi regency.. the purpose of conducting this research is.1) that influence the  influence of knowledge that on performance of BUMDes managers 2)  that  influence the skills that on performance of BUMDes managers 3) to influence the influence of attitudes on the performance of BUMDes managers on Kuantan Singingi Regency. The sample in this research were BUMDes managers which included a basic classification of 165 BUMDes with a total of 255 managers.The independent variables in this study are knowledge, skills and work attitudes, while the dependent variable is the manager's performance. The sample analysis method used is descriptive analysis, quantitative analysis is validity test, reliability test, hypothesis testing using Warp PLS program 0.7The results showed that 1) Knowledge variable (X1) has an effect but not significant on performance (Y) because its significance value was 0.06. This value is greater than the alpha value of 0.05.2) Skills (X2) and Work Attitude (X3) variables have a significant  on performance (Y) because the significance value is <0.01. the value are smaller than the alpha value of 0.05; 3) Of the two independent variables that have a significant effect, the Skills variable (X2) is the independent variables owned as the clear influence on performance  (Y) because it has the largest path coefficient value, ie 0.22; Keywords: Knowledge, skills, work attitude and manager performance.